Hubungan Kadar Plasma Leptin dan Fungsi Kognitif pada Lanjut Usia di Jakarta - Pratiwi, Sandi Puspita; Mudjihartini, Ninik; Lestari, Wiji; Prawirohajo, Pukovisa (PERDOSNI, 2024)
Introduction: The increasing of elderly population often accopanied by a rise in cognitive disorders. Leptin is known to have a protective function against cognitive dectine in elderly. However, current finding regarding the role of leptin in cognitive function is vary, and has not been extensively discussed in Indonesia. Food record and antropometric assesment is conducted as an aditional analyses on subject. Aim: To determine the relationship between plasma leptin levels and cognitive function in the elderly in Jakarta. Methods: This is a cross sectional descriptive analytical research using purposive sampling as the sampling method. Subject are elderly residing in social welfare home, and being assessed using MOCA-INA instrument, IADL and GPAQ questionnaire, plasma leptin, body composition, antropometric and Food Record are measured. The data is analyzed through univariate, bivariate and multivariate analysis. Results: Subject characteristic of age ranging from 60-74 years, with female as the majority (67.5%), normal nutritional status (46.2%), body fat ranging from 18.10 to 57.10 %, muscele mass 20.20 to 57.50 kg. Majority of subject do not smoke, have a low education level (≤ 12 year of education), engage in moderate physical activity, and having independent functional capacity. A total of 96.2% of the subject experience cognitive impairment. Plasma leptin levels ranging from 1.4 to 8.5 ng/mL, with median of 5.9 ng/mL. There is a significant relationship between leptin levels, body mass index, body weight, total body fat, education and IADL with cognitive function in the elderly in Jakarta. Discussion: The correlation between plasma leptin levels and cognitive function in the elderly in Jakarta, shows a moderately positive correlation with r value of 0.47 and a significance of 0.000. Keywords: Cognitive function, Elderly, Leptin